Single-photon test of hyper-complex quantum theories using a metamaterial - Lorenzo M. Procopio (Nature Portfolio, 2017)
Hyper-complex quantum theories are generalizations of quantum mechanics where amplitudes are generalized complex numbers. Here the authors study phase commutation in a photonic experiment, reporting consistency with standard quantum mechanics and placing precise bounds on hyper-complex theories.